2017
DOI: 10.18203/2349-2902.isj20173896
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of surgical site infection in general surgery in a tertiary care centre in India

Abstract: Background: Surgical site infection (SSI) can be defined as an infection that is present up to 30 days after a surgical procedure if no implants are placed and up to one year if an implantable device was placed in the patient. SSI is a significant problem associated with major surgeries and is the 3rd most frequently reported nosocomial infection. This study aims to study the prevalence of SSI in the Department of Surgery, Rajendra Institute of Medical Sciences (RIMS), Ranchi.Methods: A retrospective study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 9 publications
0
30
1
Order By: Relevance
“…Based on bacterial pathogen estimation, the most common identified pathogen was S. aureus. The same report from India [46], Nigeria [12], and Uganda [47] showed that S.aureus found the most common causes of SSI. This might be due to S.aureus is part of human skin Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based on bacterial pathogen estimation, the most common identified pathogen was S. aureus. The same report from India [46], Nigeria [12], and Uganda [47] showed that S.aureus found the most common causes of SSI. This might be due to S.aureus is part of human skin Fig.…”
Section: Discussionmentioning
confidence: 99%
“…8 Kumar et al in a similar study reported the incidence rate of SSI as high as 12.5% but in our study the incidence of SSI was only 4%. 9 Although infection rate varying from 20% to as high as 76.9% have been reported. Our rates are comparable to studies done in United Kingdom (3.1%) and Netherlands (4.3%).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Global incidence rates of SSIs vary from 4.5% to 20%, depending on the region and facilities available and 12.5% to 17.7% in India according to one study. 3,4 Suture materials used for treating wounds were originally natural materials, such as animal tendons and cotton fibres. Usage of these materials often resulted in severe infections.…”
Section: Introductionmentioning
confidence: 99%